Pengembangan Rencana Pelaksanaan Pembelajaran (RPP) Menggunakan Model Cooperative Learning tipe Jigsaw Pada Pembelajaran Tematik Di Kelas V SD Negeri Kota Bengkulu - Toto Ronalto; Sri Dadi; Victoria Karjiyati (Universitas Bengkulu, 2021)
This study aims to produce a Learning Implementation Plan (RPP) using the Jigsaw Cooperative Learning model in grade V Elementary School (SD) which is feasible in the learning process in the classroom. This study is a Research and Development (R&D) research by modifying the 4-D model. However, this research was only carried out until the third stage, namely Definition, Design and Development. Validation is carried out by learning design experts, learning material experts and language experts. The lesson plans developed were given scores and responses by 8 SD Negeri Bengkulu City teachers to assess the products developed from the presentation and material aspects. The research subject was a grade V teacher at SDN Kota Bengkulu. The data analysis technique uses descriptive statistical analysis of the results of expert validation assessments and teacher responses as well as qualitative descriptive analysis of comments from expert validation and teacher responses. This study produces a Teaching Implementation Plan (RPP) model using the Jigsaw Cooperative Learning model with validation assessments from 3 experts with an average of 91.63 with a very good category. The teacher's response was 92.03 with very good category. So, the research that has been carried out can be concluded that the lesson plan using the Jigsaw Cooperative Learning model in thematic learning in grade V SD can be categorized as a very good lesson plan and can be used in learning at school.Keywords: RPP, Development, Jigsaw Cooperative Learning, Thematic